Loading....
Coupon Accepted Successfully!

 

Worked Examples

Example-1
6 8 (5)
14 7 (10)
13 6 (-)
a b c

 

Solution

Consider the numbers in the first row. Multiply the first two numbers, i.e., 6 × 8, and add 2 to the product. Now, divide the result by 10. You will get the third number.

 

Formula: (a × b + 2) ÷ 10 = c

 

(6 × 8) + 2 = 50; 50 ÷ 10 = 5

 

(14 × 7) + 2 = 100; 100 ÷ 10 = 10

 

(13 × 6) + 2 = 80; 80 ÷ 10 = 8

 

Answer: 8
 

 

Example-2
140 29 (13)
82 18 (10)
120 24 (-)
a b c

 

Solution

The third number in each row is the square root of the sum of the first two numbers.

 

Formula: Description: 76031.png

 

140 + 29 = 169; Description: 76041.png

 

82 + 18 = 100; Description: 76049.png

 

120 + 24 = 144; Description: 76056.png

 

Answer: 12
 

 

Example-3
(111) 128 94
(132) 156 108
(–) 87 165

 

Solution

The first number in each row is half the sum of the second and the third numbers.

 

Formula: Description: 76070.png

 

(128 + 94) ÷ 2 = 111

 

(156 + 108) ÷ 2 = 132

 

(87 + 165) ÷ 2 = 126

 

Answer: 126
 

 

Example-4
25 81 (196)
16 49 (121)
64 100 (-)

 

Solution

The third number in each row is the square of the sum of the square roots of the first and second numbers.

 

Formula: Description: 76107.png

 

Description: 76123.png = 5; Description: 76147.png = 9; 5 + 9 = 14; 142 = 196

 

Description: 76131.png = 4; Description: 76162.png = 7; 4 + 7 = 11; 112 = 121

 

Description: 76138.png = 8; Description: 76170.png = 10; 8 + 10 = 18; 182 = 324

 

Answer: 324
 

 

Example-5
7 5 (36)
9 1 (25)
12 4 (-)

 

Solution

The third number in each row is the square of half of the sum of the first and second numbers.

 

Formula: Description: 76191.png

 

7 + 5 = 12; 12 ÷ 2 = 6; 62 = 36

 

9 + 1 = 10; 10 ÷ 2 = 5; 52 = 25

 

12 + 4 = 16; 16 ÷ 2 = 8; 82 = 64

 

Answer: 64
 

 

Example-6
4 6 (26)
7 3 (29)
3 9 (-)

Solution

The third number in each row is half the sum of the squares of the first and second numbers.

 

Formula: Description: 76210.png

 

42 = 16; 62 = 36; 16 + 36 = 52; 52 ÷ 2 = 26

 

72 = 49; 32 = 9; 49 + 9 = 58; 58 ÷ 2 = 29

 

32 = 9; 92 = 81; 9 + 81 = 90; 90 ÷ 2 = 45

 

Answer: 45

 

Example-7
36 (23) 15
29 (39) 37
47 (-) 53

Solution

The second number, in each row, is the sum of the products of the digits of the first and second numbers.

 

Formula: POD of a + POD of c = b

 

POD of 36 = 3 × 6 = 18; POD of 15 = 1 × 5 = 5; 18 + 5 = 23

 

POD of 29 = 2 × 9 = 18; POD of 37 = 3 × 7 = 21; 18 + 21 = 39

 

POD of 47 = 4 × 7 = 28; POD of 53 = 5 × 3 = 15; 28 + 15 = 43

 

Answer: 43
 

 

Example-8
14 4 (30)
8 12 (22)
19 14 (-)

 

Solution

The third number in each row is the sum of twice the first number and half the second number.

 

Formula: Description: 76244.png

 

(14 × 2) + (4 ÷ 2) = 28 + 2 = 30

 

(8 × 2) + (12 ÷ 2) = 16 + 6 = 22

 

(19 × 2) + (14 ÷ 2) = 38 + 7 = 45

 

Answer: 45
 

 

Example-9
6 4 (100)
8 5 (189)
11 3 (-)

Solution

The third number in each row is the sum of the square of the first number and the cube of the second number.

 

Formula: a2 + b3 = c

 

62 + 43 = 36 + 64 = 100

 

82 + 53 = 64 + 125 = 189

 

112 + 33 = 121 + 27 = 148

 

Answer: 148
 

 

Example-10
14 11 (75)
11 7 (72)
10 6 (-)

Solution

The third number in each row is the difference between the squares of the first and second numbers.

 

Formula: a2 – b2 = c

 

142 = 196; 112 = 121; 196 – 121 = 75

 

112 = 121; 72 = 49; 121 – 49 = 72

 

102 = 100; 62 = 36; 100 – 36 = 64

 

Answer: 64
 


Example-11
8 6 (72)
5 12 (90)
12 9 (-)

Solution

The third number in each row is one and half (or 3/2) times the product of the first two numbers.

 

Formula: Description: 76303.png

 

8 × 6 = 48; Description: 76311.png × 48 = 72

 

5 × 12 = 60; Description: 76315.png × 60 = 90

 

12 × 9 = 108; Description: 76320.png × 108 = 162

 

Answer: 162
 

 

Example-12
7 9 (41)
8 6 (34)
9 5 (-)

Solution

The third number in each row is the sum of twice the first number and thrice the second number.

 

Formula: 2a + 3b = c

 

(7 × 2) + (9 × 3) = 14 + 27 = 41

 

(8 × 2) + (6 × 3) = 16 + 18 = 34

 

(9 × 2) + (5 × 3) = 18 + 15 = 33

 

Answer: 33
 

 

Example-13
14 6 (50)
11 9 (92)
12 7 (-)

Solution

The third number in each row is the sum of the first number plus the square of the second number.

 

Formula: a + b2 = c

 

14 + 62 = 14 + 36 = 50

 

11 + 92 = 11 + 81 = 92

 

12 + 72 = 12 + 49 = 61

 

Answer: 61
 

 

Example-14
39 (3) 12
54 (2) 46
184 (-) 59

Solution

The second number in each row is the cube root of the difference between the first and the third numbers.

 

Formula: Description: 76364.png

 

39 – 12 = 27; Description: 76380.png = 3

 

54 – 46 = 8; Description: 76389.png = 2

 

184 – 59 = 125; Description: 76398.png = 5

 

Answer: 5
 

 

Example-15
272 151 (11)
308 227 (9)
195 131 (-)

Solution

The third number in each row is the square root of the difference between the first and second numbers.

 

Formula: Description: 76416.png

 

272 – 151 = 121; Description: 76432.png = 11

 

308 – 227 = 81; Description: 76440.png = 9

 

195 – 131 = 64; Description: 76447.png = 8

 

Answer: 8
 

 

Example-16
17 (11) 36
21 (13) 64
19 (-) 25
 
Solution

The second number in each row is the difference between the first number and the square root of the third number.

 

Formula: Description: 76460.png

 

17 – Description: 76487.png = 17 – 6 = 11

 

21 – Description: 76492.png = 21 – 8 = 13

 

19 – Description: 76505.png = 19 – 5 = 14

 

Answer: 14
 


Example-17
36 49 (117)
23 36 (45)
45 57 (-)
 
Solution

The third number in each row is the product of SOD (sum of digits) of the first and second numbers.

 

Formula: SOD of a × SOD of b = c

 

3 + 6 = 9; 4 + 9 = 13; 9 × 13 = 117

 

2 + 3 = 5; 3 + 6 = 9; 5 × 9 = 45

 

4 + 5 = 9; 5 + 7 = 12; 9 × 12 = 108

 

Answer: 108
 

 

Example-18
916 (166) 976
971 (177) 879
245 (-) 555

 

Solution

Sum of digits of the first number and the difference between SOD of the third and first numbers are written side by side to get the second number.

 

Consider the numbers in the first row.

 

SOD of 916 = 9 + 1 + 6 = 16; SOD of 976 = 9 + 7 + 6 = 22; 22 – 16 = 6

 

If you write 16 and 6 side by side, you get 166, which is the second number.

 

Consider the numbers in the second row.

 

SOD of 971 = 9 + 7 + 1 = 17; SOD of 879 = 8 + 7 + 9 = 24; 24 – 17 = 7

 

On writing 17 and 7 side by side you get 177.

 

Consider the numbers in the third row.

 

SOD of 245 = 2 + 4 + 5 = 11; SOD of 555 = 5 + 5 + 5 = 15; 15 – 11 = 4

 

On writing 11 and 4 side by side you get 114.

 

Answer: 114
 

 

Example-19
213 (180) 534
352 (-) 612
 
Solution

Formula: (SOD of a + SOD of c) × 10 = b

 

SOD of 213 = 2 + 1 + 3 = 6; SOD of 534 = 5 + 3 + 4 = 12; (12 + 6) × 10 = 180

 

SOD of 352 = 3 + 5 + 2 = 10; SOD of 612 = 6 + 1 + 2 = 9; (10 + 9) × 10 = 190

 

Answer: 190
 





Test Your Skills Now!
Take a Quiz now
Reviewer Name